2001
DOI: 10.1128/jvi.75.5.2204-2212.2001
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Mammalian Cell Line Continuously Expressing Japanese Encephalitis Virus Subviral Particles

Abstract: We have generated a cell line (F cells) producing a secreted form of Japanese encephalitis virus (JEV) subviral particle (extracellular particles [EPs]) that contains the JEV envelope glycoprotein (E) and a precursor (prM) of the virion membrane protein (M). The F cells were engineered to synthesize these JEV products from a cDNA encoding a mutated (furin proteinase resistant) form of prM, since stable cell lines expressing E and the authentic form of prM could not be obtained, due (in part) to the cell-fusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 38 publications
1
90
0
Order By: Relevance
“…During flavivirus virion maturation, the cleavage from prM to M causes the rearrangement of E proteins on virus particles, leading to the formation of mature virions that can show cell-fusion activity. As reported previously for mammalian cells, 5,6 the use of the gene encoding a mutated (furin proteinase resistant) form of prM was effective in generating highly productive recombinant insect cells. Finally, suspension culture was useful in improving productivity.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…During flavivirus virion maturation, the cleavage from prM to M causes the rearrangement of E proteins on virus particles, leading to the formation of mature virions that can show cell-fusion activity. As reported previously for mammalian cells, 5,6 the use of the gene encoding a mutated (furin proteinase resistant) form of prM was effective in generating highly productive recombinant insect cells. Finally, suspension culture was useful in improving productivity.…”
mentioning
confidence: 84%
“…VLPs are a highly effective type of subunit vaccine that can elicit strong immune responses because of their repeated dense display of viral antigens in an authentic conformation. [3][4][5][6][7] Therefore, VLPs offer a promising approach to the development of safe and efficacious vaccines and diagnostic antigens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that high level expression of VLPs could result in fusion, apoptosis, and death in some JEV susceptible cells (Kojima et al, 2003;Konishi et al, 2001). In this study, apoptosis induced by JEV VLPs was found in pCprME transfected 293FT cells, which suggested that the VLPs were also toxic for this cell line.…”
Section: Discussionmentioning
confidence: 51%
“…2A) and the envelope (E1-E2) sequences separatly. Although some subviral enveloped particles lacking cores have been described for other Flaviviridae such as the Japanese encephalitis virus (Konishi et al, 2001), HCV E1-E2 production did not result in the detection of particles by EM (unpublished data). However, production of the core protein alone resulted in the budding of VLPs towards the ER lumen, and the detection of electrondense areas lining the cytosolic side of the ER lumen (Blanchard et al, 2003b).…”
Section: The Virus-like Particle (Vlp) Modelmentioning
confidence: 99%